2013
DOI: 10.4103/1947-2714.122303
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment in prediabetes and undiagnosed diabetes mellitus study: International collaboration research overview

Abstract: The study aims to develop a screening protocol for the risk of future cardiovascular disease and diabetes mellitus in people with prediabetes and undiagnosed diabetes; and to establish a framework for early identification and intervention of prediabetes including strategies for holistic management and monitoring of progression. The first phase is to identify prediabetes and undiagnosed diabetes in volunteers who are ≥18-years-old for 5 years. Point-of-care testing and questionnaire will be used to screen for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…63 More so, there is call to assess the potential of possible screening of individuals less than 40 years old. 64 Type of studies and subpopulations studied: each of the 32 studies assessed revealed significant prevalence of CMS in Nigeria. However, no longitudinal study was found on the CMS studies done in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…63 More so, there is call to assess the potential of possible screening of individuals less than 40 years old. 64 Type of studies and subpopulations studied: each of the 32 studies assessed revealed significant prevalence of CMS in Nigeria. However, no longitudinal study was found on the CMS studies done in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular risk assessment in prediabetes and undiagnosed diabetes mellitus study has been identified as necessary, especially for low-mid income communities [1]. To substantiate the discussion of prediabetes and cardiovascular disease (CVD), a systematic review had been performed that provided insight, for instance, the need to study rural communities where lifestyles are different from the urban areas [2].…”
Section: Introductionmentioning
confidence: 99%
“…1) [4–6]. As published [1], the aims of the ‘prediabetes and cardiovascular complications studies (PACCS) collaboration initiative are:
Fig. 1Estimated global burden and deaths due to CVD.
…”
Section: Introductionmentioning
confidence: 99%
“…As indicated in the proposal of my international research collaboration [58], about 80% of CVD deaths worldwide take place in developing, low-, and middle-income countries, and these countries also account for 86% of the global CVD burden [59À61]. Some of the low-to middleincome countries are currently undergoing rapid epidemiological transition in metabolic disorders [62], and demographic changes such as aging, and the undesirable risk factors such as obesity and sedentary life, have been implicated as causes [63À66].…”
Section: Programs For Identification Of Pre-diabetes and Udm Are Limitedmentioning
confidence: 98%
“…The hypothesis is that high schools and churches should be approached for public health lectures to target individuals who are 18 years old or older [58]. With the collaboration of primary healthcare departments at the local government level, population screening for pre-diabetes and UDM can be done with point-of-care (POCT) blood glucose devices.…”
Section: Strategy For Early and Improved Identification Of Pre-diabetesmentioning
confidence: 99%